'Everyday conservation': a study of actors and processes in an elephant conservation project in Assam, India. Issue 6 (2nd November 2022) - Banerjee, Sayan; Aiyadurai, Ambika
ABSTRACT: Existing studies on community-based conservation in India, while highlighting the results and effectiveness of conservation interventions fail to engage with the underlining social processes emerging from the interactions among conservation actors. This article demonstrates conservation as a social process in which the actors interact with each other daily. We use the notion of 'Everyday Conservation' to highlight that actors use their resources, skills and limitations to create a space where conservation processes are negotiated and shaped on an everyday basis. Using ethnographic work carried out in Assam (India), this article analyzes an Asian elephant conservation project to understand the various actors involved in the project, such as project managers, staff, local community, funding organization and forest department and their interactions, resulting in 'Everyday Conservation.' The inter-actor interactions were of varying intensity, depending upon which the actors negotiated, collaborated, or came into conflict, thereby producing conservation results embedded in contextual factors. We suggest that conservation needs rethinking and the framework of 'Everyday Conservation' can provide a fresh perspective on community-based wildlife conservation.